Gaya Kepemimpinan Sekretaris Dewan Dalam Meningkatkan Kinerja Aparatur Sipil Negara Pada Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Tabanan - Ni Luh Putu Dian Sartini; I Gst Ngr Ag Bgs Widiana (Jurnal Widya Mahavira, 2025)
This study analyzes the leadership style of the Secretary of the Council in improving the performance of the State Civil Apparatus (ASN) at the Secretariat of the Tabanan Regency DPRD. Using a qualitative descriptive method with the leadership style theory of Lippit and White, this study examines three leadership styles: autocratic, democratic, and laissez-faire. The results of the study show that the Secretary of the Council implements a democratic leadership style that has proven effective in improving the performance of ASN. The inhibiting factors identified include changing situational conditions and the leader's indecisiveness in dealing with subordinates. Meanwhile, supporting factors include the availability of adequate budgets, supporting infrastructure, quality human resources, and good communication and motivation from leaders. Effective communication and motivation provided by leaders create comfort and work spirit for subordinates, so that activities at the Tabanan Regency DPRD Secretariat can be carried out optimally. Based on the indicators studied, the democratic leadership style applied has been running well and can be said to be effective and efficient in improving the performance of civil servants.